Restoration of the Production in a Dead Well by using Low Cost Recompletion of Sand Control - Bouba, Apollinaire; Nitcheu, Madeleine; Karga, Lionel Tapsia; Oumate, Alhadji Abba; Nana, Souleymanou Baba; Ngueyep, Luc Leroy Mambou (Peneliti Teknologi Teknik Indonesia, 2023)
This paper proposes a cost-effective solution through a recompletion design of sand control to restart the production of a dead well named